Changes in the Hungarian law and in the classification system regarding to ’people living with disabilities’ between 2008 and 2013 - Nagymáté, Nóra (Acta Agraria Debreceniensis, 2013)
Nowadays employment is a hot topic in Hungary. The rate of inactive people on the labour market is very high. Many kinds of supplies are provided by the State for example for the group “people living with disabilities”. It is very difficult to provide job for these people after their rehabilitation. Statistical figures show, that the highest ratio of “people living with disabilities” can be found in the North Great Plain Region of Hungary (30 per cent of the total number of “people living with disabilities”).The employment of these people means extra costs for enterprises. At the same time the complete accessibility of workplaces is still not realized in many cases in Hungary yet. Currently only a few enterprises are specialized to employ people living with disabilities in the North Great Plain Region. Unfortunately most of the enterprises don’t want to employ them. New workplaces for these people should be created by the utilisation of European Union and national available sources in order to integrate them into the job’s world in long run. I represent the changes in the law and in the classification system in this area.